Analisis Strategi Konten Local Pride @batiksemarang16 dalam Membentuk Brand Awarness - Saptiyono, Ami; Retno Manuhoro Steyowati; B Natalia Sari Pujiastuti (LPPM Stikosa - AWS, 2025)
This research is a qualitative research conducted by observing the content of the @batiksemarang16 Instagram account content, related to local pride, to analyse what kind of content strategy is carried out by the account manager in forming brand awareness from the public, especially its followers. The content in the @batiksearang16 account was selected and taken using purposive sampling based on the criteria of the object under study, consisting of posts uploaded between April 2024 and June 2024, having likes above 25, not posts in the form of sales or direct promotion, and related to local pride. The findings from observations and literature studies of previous research obtained by researchers, then analysed using the theory of 4 content pillar social media, where the results of posts in the @batiksemarang16 Instagram account, have implemented the four pillars in the 4 pillars Social Media Strategy, this can be seen from the content uploaded by the account manager @batiksemarang16, always communicating local pride in building brand awareness of the community. in addition, the content of the account content, showing the collaboration that occurs between the manager and external parties within the scope of local pride to support pm although in terms of entertainment it is still less than optimal in forming Brand Awarness to the public within the scope of the Local Pride campaign.